Morphological Features of Ewing Sarcoma Post-Neoadjuvant Therapy and Their Impact on Prognosis - Atique, Usman; Mushtaq, Sajid; Rana, Iftikhar Ali; Hassan, Usman (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the effect of chemotherapeutic response on resection specimens and to assess their effect on prognosis. Study Design: Retrospective longitudinal study. Place and Duration of Study: Shaukat Khanum Memorial Cancer Hospital and Research Centre, Peshawar Pakistan, from Jan 2010 to Mar 2018. Methodology: This study included 42 cases of Ewing sarcoma diagnosed, treated and followed at our institute. Various diagnostic parameters were noted and were assessed for their impact on two-year overall survival, development of distant metastasis, recurrence and cancer-related death. Results: This study included 28 males and 14 females. The majority involved long bones followed by the axial skeleton and soft tissue. Nine cases (9) were confirmed by molecular testing. On the post-neoadjuvant chemotherapy resection specimens, 45% cases had Huvos grade I necrosis, 17% had grade-II, 12% had grade-III and 26% cases had Huvos grade-IV necrosis. Increasing Huvos grade was associated with improved disease-free survival (21%, 43% and 69% for grades-I, II and III/IV respectively). The site and size did not significantly affect the development of recurrence, development of metastasis, or twoyear survival (p>0.05). Conclusion: Meticulous assessment of post neoadjuvant resection specimens for necrosis provides helpful information about the prognostic outcome. Increasing grade of tumour necrosis was associated with increasing disease-free survival. The response to chemotherapy in our study population was worse than Western data, which may be linked to a variety of factors.